UJI DAYA ANTIINFLAMASI EKSTRAK ETANOLIK DAUN MONDOKAKI (Tabernaemontana divaricata, R.Br.) PADA TIKUS PUTIH JANTAN - Jason Merari Peranginangin (Jurnal Farmasi Indonesia, 2009)
Mondokaki plant (Tabernaemontana divaricata, R.Br.) is a traditional medicine used in medicating high blood pressure, pharyngitis, conjunctivitis, mastitis, mad dog bite, antitusissive, anti-inflammatoty and sprain. The aim of the research was to know the anti-inflammatory effect of mondokaki leaves ethanolic extract on male shite rat. Mondokaki leaves were extracted using ethanol 70% by maceration method. The extract was tested to each group of the rat with doses of 3.75 mg/200 g bw, 7.5 mg/200 g bw, 15 mg/200 g bw. The negative control group was given CMC 0.5% solution and the positive control group was given sodium diclofenac as antiinflammatory agent. The compounds were all given orally one hour before the rat plantar was injected with carragenin 1% to make edema. The anti-inflammatory effect was observed from the ability to reduce edema volume at one hour interval for five hours. One way analysis of varian at 95% confidence was done to know the difference in each treatment and LSD test was done to know the difference between the treatment groups. The result of the research showed that ethanolic extract of 15 mg/200 g bw dose did not significantly different compared with the positive control. It was indicated that ethanolic extract of 15% mg/200 g bw dose had anti-inflammatory effect by reducing edema volume of male white rat in proportion with the positive control.